Pentingnya Penerapan Metode FIFO Dalam Meningkatkan Standar Kualitas Produk Pastry Di Hotel Sheraton Grand Jakarta - Martinus Hia; Donant Alananto Iskandar (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study examines the importance and effectiveness of implementing the First-In-First-Out,  inventory method in the pastry kitchen of Sheraton Grand Jakarta to improve product quality, reduce food waste, and enhance operational efficiency. Using a descriptive qualitative case-study approach, data were collected through structured observations, semi-structured interviews with pastry staff at multiple hierarchical levels, SOP review, pastry product quality assessment. The findings reveal that although pastry staff demonstrate strong conceptual understanding of FIFO, its practical implementation remains inconsistent. Key barriers include incomplete labeling, ineffective storage layout, unclear responsibility for stock rotation, and limited routine supervision. Inconsistent FIFO application was associated with sensory quality issues—particularly aroma degradation in dairy-based products and increased avoidable waste. Conversely, consistent FIFO adherence resulted in more uniform taste, texture, lower discard rates, smoother production flow. The study recommends standardized labeling, zoned storage systems, clear accountability per shift, targeted training, integration of FIFO checks into HACCP procedures.